45 SPIRONOLACTONE IN THE PREVENTION OF SKELETAL MUSCLE ATROPHY AND BONE LOSS IN RATS WITH ALDOSTERONISM. Issue 1 (1st January 2007) - Roberts, M.; Sun, Y.; Bhattacharya, S. K.; Ahokas, R. A.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: Congestive heart failure (CHF), with its classic signs and symptoms, has its origins rooted in a salt-avid state mediated largely by effector hormones of the renin-angiotensin-aldosterone system (RAAS). CHF is accompanied by a systemic illness that features oxidative stress and a progressive loss of soft tissues and bone that eventuates in a wasting syndrome termed cardiac cachexia. To simulate the inappropriate (relative to dietary Na + ) aldosteronism found in human CHF, rats receive aldosterone (0.75 μg/h), together with 1% NaCl in drinking water (ALDOST). Skeletal muscle wasting and bone loss are found in ALDOST and associated with secondary hyperparathyroidism (SHPT). Herein we hypothesized that these responses could be attenuated by cotreatment with spironolactone (Spiro), an ALDO receptor antagonist. Methods and Results: Eight-week-old male Sprague-Dawley rats received ALDOST alone for 4 weeks or together with Spiro (150 mg/kg/d by gavage). We monitored: body weight and skeletal muscle morphology, including scarring, a marker of myocyte necrosis, and the presence of apoptosis (TUNEL assay); femoral bone mineral density (BMD) and content (BMC); plasma α1 -antiproteinase activity (AP), an inverse correlate of oxidative stress; and plasma parathyroid hormone (PTH). Compared with age-/gender-matched controls, with ALDOST we found (mean ± SEM): inadequate weight gain (81 ± 5 vs 22 ± 6 g; p < .05) accompanied by skeletal muscle atrophy without evidence of myocyte apoptosis or necrosis; a fall ( p < .05) in BMD (0.162 ± 0.002 vs 0.151 ± 0.003 g/cm 2 ) and BMC (0.420 ± 0.012 vs 0.336 ± 0.008 g); a fall ( p < .05) in α1 -AP activity (39.8 ± 2.1 vs 24.3 ± 1.2 μmol/L); and elevation ( p < .05) in plasma PTH (10.6 ± 0.9 vs 16.0 ± 1.6 pg/mL). In response to cotreatment with Spiro, weight gain was closer to controls (+56 ± 7 g); the loss of BMD (0.162 ± 0.003 g/cm 2 ) and BMC (0.369 ± 0.006 g), the fall in α1 -AP activity (33.8 ± 1.2 μmol/L), and the rise in PTH (9.4 [138